Impact of A1 and A2 Β-Casein Variants on Human Health: Is Β-Casomorphin-7 A Detrimental Peptide in Cow’s Milk - Kabir, Abdul; Ishfaq, Ihtisham; Bashir, Anam; Ali Khan, Wajid; Anees ur Rahman,; Ali, Muzaffar; Hafeez Bukero, Abdul; Ali Mari, Firdous; Shah, Shafiq ur Rahman (Indus Journal of Bioscience Research, 2024)
This review explores the effects of cow milk containing A1, A2, or mixed variants of β-casein on human health. Data were collected from reputable scientific databases, including Scopus, PubMed, and Google Scholar, using specific keywords such as "cow milk," "A1A2 beta-casein," "beta-casomorphins," "A2 cow milk," and "A2 milk." A total of 200 articles, including patents, were identified, with approximately 62 of the most relevant articles critically reviewed. The literature indicates that the most common type of cow milk globally is mixed A1/A2, containing equal proportions of both β-casein variants. Among the three major categories, A2 cow milk has attracted significant attention from both the scientific community and the public due to its potential health benefits over A1 milk, particularly concerning diabetes and cardiovascular issues. Conversely, milk containing the A1 variant of β-casein is considered potentially harmful due to the formation of the β-casomorphin-7 (BCM-7) peptide, although this claim remains contentious within the scientific community. Further research is needed to substantiate the alleged harmful effects of the A1 variant.